Argentina : Detailed Assessment of Observance of Principles for Insurance Supervision. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2012)
Argentina's insurance market is fragmented, and competition has increased in recent years. Currently, excessive premium discounting by insurance companies is creating risks that insurance companies may be under-reserved and may not be able to meet future liabilities. The evolution of liability insurance is positive but will require developing specific expertise. In line with developments around the world, the adoption of a risk-based supervisory approach is essential to properly monitor a rapidly evolving market. To successfully address these challenges, additional resources as well as operational independence is required.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet